Multiple transcriptional regulation of walnut JrGSTTau1 gene in response to osmotic stress. Issue 3 (2nd October 2018) - Yang, Guiyan; Chen, Shuwen; Li, Dapei; Gao, Xiangqian; Su, Liyuan; Peng, Shaobing; Zhai, MeiZhi
Abstract : Glutathione S‐transferases (GSTs) are important plant proteins involved in biotic and abiotic stress responses. A gene from Juglans regia, JrGSTTau1 was previously cloned and functionally characterized as an enzyme involved in improving cold tolerance in plants. To clarify the functional mechanism of JrGSTTau1 and its role in stress response, here, the JrGSTTau1 promoter including the up‐stream regulators was examined using yeast one‐hybrid together with transient expression assays, and the osmotic stress response ability was confirmed by comparing with wild‐type plants. The 1500 bp JrGSTTau1 promoter displayed high GUS expression activity and was enhanced by mannitol stress. The promoter is composed of abundant cis ‐elements, some of which were osmotic stress response‐related motifs, such as ABRE, DRE and MYB, indicating that the expression of JrGSTTau1 is regulated by potential up‐stream regulators under abiotic stress. The transcription factors (TFs) of JrDREB2A, JrMYC2, JrMYB44, JrDof1 and JrWRKY7 were identified, which shared a similar response with JrGSTTau1 when exposed to PEG6000 in walnut leaf and root. These results implied that JrDREB2A, JrMYC2, JrMYB44, JrDof1 and JrWRKY7 may act as up‐stream regulators of JrGSTTau1 to regulate or combine functionality with JrGSTTau1 in osmotic stress response. Furthermore, compared with the WT plants, the transgenic tobacco plants that overexpress JrGSTTau1 showed improved tolerance to drought induced by osmotic stress, in which antioxidant enzymes, proline and reactive oxygen species (ROS) are involved. Our results demonstrated the positive role played by JrGSTTau1 in osmotic tolerance, which is regulated by multiple up‐stream regulators.